2020
DOI: 10.1038/s41598-020-79073-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of occult lymph node metastases in patients with completely resected esophageal squamous cell carcinoma

Abstract: To investigate the prognostic value of occult lymph node metastases (OLNMs) in patients with pathologically lymph node negative (pN0) esophageal squamous cell carcinoma (ESCC). OLNMs were detected in 516 pN0 ESCC patients by immunohistochemical staining. The correlation between the clinicopathological features and OLNM, and the prognostic value of OLNM was explored. Eighty-eight patients (17.1%) had OLNMs, including 37 patients with isolated tumor cells (ITCs), 49 patients with micrometastases, and 2 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Subsequently, 45 full-text manuscripts were assessed for eligibility, from which 29 did not meet the inclusion criteria and were excluded. Accordingly, only 16 studies including 1,652 patients were included ( 5 7 , 17 21 , 25 32 ) ( Figure 1 ). The study characteristics and baseline demographics are shown ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequently, 45 full-text manuscripts were assessed for eligibility, from which 29 did not meet the inclusion criteria and were excluded. Accordingly, only 16 studies including 1,652 patients were included ( 5 7 , 17 21 , 25 32 ) ( Figure 1 ). The study characteristics and baseline demographics are shown ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 944 patients were identified in seven studies ( 5 , 7 , 19 , 25 , 26 , 28 , 30 ). The RFS was significantly increased with LNM negativity compared with LNM positivity in esophageal cancer patients (HR 3.39; 95% CI, 1.87–6.16; P < 0.001; I 2 = 50.18%, P = 0.060; Figure 3 ; certainty of evidence, moderate).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sensitivity analyses incorporating N stage and grade in the multivariable Cox models revealed similar associations between metastatic pattern and survival (data available on request). The study did not include molecular profiling, which has some correlation with the outcome, 26 , 27 , 28 , 29 , 30 but it is not currently a component of stage classification. It is possible that the patients with stage IV-nodal disease had molecular characteristics that were more favorable.…”
Section: Discussionmentioning
confidence: 99%